Are Liberal Governments More Cooperative? Voting Trends at the UN in Five Anglophone Democracies. (July 2019) - Hanania, Richard
Among both elites and the mass public, conservatives and liberal differ in their foreign policy preferences. Relatively little effort, however, has been put toward showing that, beyond the use of force, these differences affect the day-to-day outputs and processes of foreign policy. This article uses United Nations voting data from 1946 to 2008 of the five major Anglophone democracies of the United States, the United Kingdom, Canada, Australia, and New Zealand to show that each of these countries votes more in line with the rest of the world when liberals are in power. This can be explained by ideological differences between conservatives and liberals and the ways in which the socializing power of international institutions interact with preexisting ideologies. The results hope to encourage more research into the ways in which ideological differences among the masses and elites translate into differences in foreign policy goals and practices across governments.